Penerapan Model Pembelajaran Personal Digital Inquiry untuk Meningkatkan Literasi Informasi Siswa pada Materi Sistem Reproduksi Manusia - Rival Arief Tyansha; Kusnadi Kusnadi; Widi Purwianingsih (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The 21st century is very closely related to science and technology, so the demands of human resources are needed in order to be able to master various forms of skills. Information literacy is a very important ability for everyone when they are in the realm of biology, especially students. However, most schools at the high school level, especially in Indonesia, often do not strategically prioritize the development of information literacy. The use of the Personal Digital Inquiry learning model on the material of the human reproductive system can be used as a way to provide students with information literacy.This research aims to analyze the effectiveness of the application of the Personal Digital Inquiry learning model in improving students' information literacy on the material of the human reproductive system. This research uses a quasi-experimental method. The research design used was a non-equivalent control group design. The sample in this research were two classes, namely students of class XI IPA, amounting to 35-40 people. The instrument used is a multiple choice information literacy test with 10 numbers related to the material of the human reproductive system. Based on the results of information literacy data obtained from the pretest and posttest scores, the experimental class experienced a higher increase than the control class. The results showed that the experimental class had a higher N-gain than the control class. This shows that the use of the Personal Digital Inquiry learning model is able to improve and train students' information literacy.